2021
DOI: 10.12688/f1000research.52051.2
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ relative immunity, or lack thereof, against COVID-19 emotional distress and psychological challenges; a descriptive study from Jordan

Abstract: Background: Emotional distress is a major impact of COVID-19 among not only the general public but also healthcare workers including medical students. This study aimed at describing self-reported changes in emotional reactions associated with COVID-19 among medical students in Jordan and to assessing the potential effect of social media utilization on emotional distress among this group. Methods: A cross-sectional design was utilized to collect data early on during the outbreak in Jordan. All medical students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…Other contributing factors to anxiety include the increase in their workload; their worries of transmitting the infection to other patients, colleagues, loved ones, and family members; the negative feelings that progressively build up as HCWs see the suffering of patients and their families; the periods of lockdown and movement restriction; and the harmful effects of the pandemic on their social support system [ 23 , 24 , 25 , 26 ]. Thus, HCWs are vulnerable to this psychopathological stress, increasing symptoms of depression and anxiety [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other contributing factors to anxiety include the increase in their workload; their worries of transmitting the infection to other patients, colleagues, loved ones, and family members; the negative feelings that progressively build up as HCWs see the suffering of patients and their families; the periods of lockdown and movement restriction; and the harmful effects of the pandemic on their social support system [ 23 , 24 , 25 , 26 ]. Thus, HCWs are vulnerable to this psychopathological stress, increasing symptoms of depression and anxiety [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Jordan, students experienced increased insomnia, shallow sleep, nightmares or insufficient sleep, and these disorders were reported in significantly more females than males. 85 …”
Section: Resultsmentioning
confidence: 99%
“…In Jordan, students experienced increased insomnia, shallow sleep, nightmares or insufficient sleep, and these disorders were reported in significantly more females than males. 85 People with chronic illnesses A total of seven cross-sectional design studies assessed sleep health among the population with special conditions. The sample size of studies ranged from 145 to 2223 participants.…”
Section: Sleep Problemsmentioning
confidence: 99%
“…Previous studies from Jordan reported the low willingness of healthcare workers to be vaccinated against COVID-19 and exaggeration of emotional distress and psychological challenges among healthcare providers and medical students. [42][43][44][45] Another epidemiologically influential group in the current study was those with chronic diseases (13.4% of adult participants). Of which, about twothirds were vaccinated, and 82.1% were seropositive.…”
Section: Dovepressmentioning
confidence: 90%